Bacteriophage K Antimicrobial-Lock Technique for Treatment of Staphylococcus aureus Central Venous Catheter–Related Infection: A Leporine Model Efficacy Analysis - Lungren, Matthew P. (J Vasc Interv Radiol, 2014)
PURPOSE: To determine whether a bacteriophage antimicrobial-lock technique can reduce bacterial colonization and biofilm formation on indwelling central venous catheters in a rabbit model. MATERIALS AND METHODS: Cuffed central venous catheters were inserted into the jugular vein of female New Zealand White rabbits under image guidance. Catheters were inoculated for 24 hours with broth culture of methicillin-sensitive Staphylococcus aureus. The inoculum was aspirated, and rabbits were randomly assigned to two equal groups for 24 hours: (i) untreated controls (heparinized saline lock), (ii) bacteriophage antimicrobial-lock (staphylococcal bacteriophage K, propagated titer > 10(8)/mL). Blood cultures were obtained via peripheral veins, and the catheters were removed for quantitative culture and scanning electron microscopy. RESULTS: Mean colony-forming units (CFU) per cm(2) of the distal catheter segment, as a measure of biofilm, were significantly decreased in experimental animals compared with controls (control, 1.2 × 10(5) CFU/cm(2); experimental, 7.6 × 10(3); P = .016). Scanning electron microscopy demonstrated that biofilms were present on the surface of five of five control catheters but only one of five treated catheters (P = .048). Blood culture results were not significantly different between the groups. CONCLUSIONS: In a rabbit model, treatment of infected central venous catheters with a bacteriophage antimicrobial-lock technique significantly reduced bacterial colonization and biofilm presence. Our data represent a preliminary step toward use of bacteriophage therapy for prevention and treatment of central venous catheter–associated infection.